2023
DOI: 10.1097/corr.0000000000002768
|View full text |Cite
|
Sign up to set email alerts
|

Which Acetabular Measurements Most Accurately Differentiate Between Patients and Controls? A Comparative Study

Abstract: Background Acetabular morphology is an important determinant of hip biomechanics. To identify features of acetabular morphology that may be associated with the development of hip symptoms while accounting for spinopelvic characteristics, one needs to determine acetabular characteristics in a group of individuals older than 45 years without symptoms or signs of osteoarthritis. Previous studied have used patients with unknown physical status to define morphological thresholds to guide management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The Acetabular Angle is determined in our study by the horizontal plane of the pelvis, which unions the inferior margins of the bilateral teardrops, and a second line that extends through the outermost point of the acetabular roof [45] (Figure 2). Consequently, the presence of joint osteoarthritis and osteophyte formation increases its values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Acetabular Angle is determined in our study by the horizontal plane of the pelvis, which unions the inferior margins of the bilateral teardrops, and a second line that extends through the outermost point of the acetabular roof [45] (Figure 2). Consequently, the presence of joint osteoarthritis and osteophyte formation increases its values.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of our consideration of the Wiberg angle and the Tonnis classification of osteoarthritis, we, along with Rotem et al [44], did not establish any association with the concrete fracture type. The Acetabular Angle is determined in our study by the horizontal plane of the pelvis, which unions the inferior margins of the bilateral teardrops, and a second line that extends through the outermost point of the acetabular roof [45] (Figure 2). Consequently, the presence of joint osteoarthritis and osteophyte formation increases its values.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Clinical Orthopaedics and Related Research ®, Verhaegen et al [10] included the patient’s activity status, spinopelvic parameters, functional anteversion, and CT measurements; they compared the asymptomatic hips with a symptomatic cohort to try to identify parameters more likely to be associated with painful hips. Anatomical and functional acetabular anteversion of 24° and 22° with a pelvic tilt of 10° were associated with more impingement-free flexion while providing sufficient posterosuperior coverage, which also was found to be important.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…They also suggested that functional anteversion is more important in determining treatment, as it has been found to be strongly associated with pelvic tilt; assessment of pelvic mobility is very important before deciding the treatment of hip version abnormalities [1]. In this issue of Clinical Orthopaedics and Related Research ® , Verhaegen et al [10] included the patient's activity status, spinopelvic parameters, functional anteversion, and CT measurements; they compared the asymptomatic hips with a symptomatic cohort to try to identify parameters more likely to be associated with painful hips. Anatomical and functional acetabular anteversion of 24°and 22°with a pelvic tilt of 10°were associated with more impingement-free flexion while providing sufficient posterosuperior coverage, which also was found to be important.…”
mentioning
confidence: 99%